2021
DOI: 10.5812/pedinfect.110603
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Neonates, A Case Series Study from Tertiary Neonatal Centers in Iran

Abstract: Introduction: The Novel coronavirus, sars-cov-2, is responsible for the recent pandemic. Although it mostly affects adults, children of all ages, including neonates, can become ill with Covid-19, as well. The real prevalence rate of coronavirus disease 2019 (COVID-19) in children is unknown. However, the severity of symptoms in children and neonates is less than in adults. Regarding the new presentation of this disease, the current study has reported a case series of COVID-19 in neonates. Case Presentation: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
1
1
Order By: Relevance
“…The abnormal radiological findings reported by Ilaria Liguoro et al [ 7 ] and by Tabatabaei [ 9 ] were detected in less than half of our cases, yet specific lesions were not so common. In a systematic review by Ilaria Liguoro et al, less than half of the neonates (48%) had abnormal findings in chest radiography, whereas only one of our cases had an abnormal CXR, including hyperinflation and stomach dilation.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The abnormal radiological findings reported by Ilaria Liguoro et al [ 7 ] and by Tabatabaei [ 9 ] were detected in less than half of our cases, yet specific lesions were not so common. In a systematic review by Ilaria Liguoro et al, less than half of the neonates (48%) had abnormal findings in chest radiography, whereas only one of our cases had an abnormal CXR, including hyperinflation and stomach dilation.…”
Section: Discussioncontrasting
confidence: 45%
“…In the study by Tabatabai, fever was reported in most of the studied patients [ 9 ]. In a survey by De Bernardo et al, the main findings at onset were fever, vomiting, cough or shortness of breath, diarrhea, lethargy, and respiratory difficulty.…”
Section: Discussionmentioning
confidence: 99%